A decade later, how much of Rwanda's musculoskeletal impairment is caused by the war in 1994 and by related violence? - Kuper, H; Atijosan, O; Rischewski, D; Simms, V; Lavy, C (2009)
BACKGROUND: In 1994 there was a horrific genocide in Rwanda following years of tension, resulting in the murder of at least 800,000 people. Although many people were injured in addition to those killed, no attempt has been made to assess the lasting burden of physical injuries related to these events. The aim of this study was to estimate the current burden of musculoskeletal impairment (MSI) attributable to the 1994 war and related violence. METHODOLOGY/PRINCIPAL FINDINGS: A national cross-sectional survey of MSI was conducted in Rwanda. 105 clusters of 80 people were selected through probability proportionate to size sampling. Households within clusters were selected through compact segment sampling. Enumerated people answered a seven-question screening test to assess whether they might have an MSI. Those who were classed as potential cases in the screening test were examined and interviewed by a physiotherapist, using a standard protocol that recorded the site, nature, cause, and severity of the MSI. People with MSI due to trauma were asked whether this trauma occurred during the 1990-1994 war or during the episodes that preceded or followed this war. Out of 8,368 people enumerated, 6,757 were available for screening and examination (80.8%). 352 people were diagnosed with an MSI (prevalence=5.2%, 95% CI=4.5-5.9%). 106 cases of MSI (30.6%) were classified as resulting from trauma, based on self-report and the physiotherapist's assessment. Of these, 14 people (13.2%) reported that their trauma-related MSI occurred during the 1990-1994 war, and a further 7 (6.6%) that their trauma-related MSI occurred during the violent episodes that preceded and followed the war, giving an overall prevalence of trauma-related MSI related to the 1990-1994 war of 0.3% (95% CI=0.2-0.4%). CONCLUSIONS/SIGNIFICANCE: A decade on, the overall prevalence of MSI was relatively high in Rwanda but few cases appeared to be the result of the 1994 war or related violence.